Country‐level and individual‐level predictors of men's support for gender equality in 42 countries. (27th August 2020) - Kosakowska‐Berezecka, Natasza; Besta, Tomasz; Bosson, Jennifer K.; Jurek, Paweł; Vandello, Joesph A.; Best, Deborah L.; Wlodarczyk, Anna; Safdar, Saba; Zawisza, Magdalena; Żadkowska, Magdalena; Sobiecki, Jurand; Agyemang, Collins Badu; et al.
Abstract: Men sometimes withdraw support for gender equality movements when their higher gender status is threatened. Here, we expand the focus of this phenomenon by examining it cross‐culturally, to test if both individual‐ and country‐level variables predict men's collective action intentions to support gender equality. We tested a model in which men's zero‐sum beliefs about gender predict reduced collective action intentions via an increase in hostile sexism. Because country‐level gender equality may threaten men's higher gender status, we also examined whether the path from zero‐sum beliefs to collective action intentions was stronger in countries higher in gender equality. Multilevel modeling on 6, 734 men from 42 countries supported the individual‐level mediation model, but found no evidence of moderation by country‐level gender equality. Both country‐level gender equality and individual‐level zero‐sum thinking independently predicted reductions in men's willingness to act collectively for gender equality.